Exploring Basic Programming Education in Primary Schools as a Foundation for Introducing Artificial Intelligence, Augmented Reality and Virtual Reality Technologies - Beauty Mugoniwa; Mampilo Phahlane; Charles Mbohwa (Politeknik Negeri Batam, 2026)
As emerging technologies such as artificial intelligence (AI), augmented reality (AR), virtual reality (VR) become increasingly integrated into educational context, primary school children need to be equipped with basic programming principles so that they can then be engaged in more advanced applications. The study guided by Pedagogical Content Knowledge (PCK) and a conceptual framework, conducted an SLR to investigate the basic programming courses designed for primary school children. The aim of the study is to evaluate how these basic principles support cognitive development and technological readiness in relation to AI/AR/VR education and its applications. Article search was conducted in Scopus, ERIC, IEEE Xplore, ACM digital library for peer reviewed articles and Google Scholar for more supporting literature published between 2018 to 2025. The combination of SPAR-4-SLR and PRISMA methods was employed to ensure rigor in article selection, screening and compilation of findings. In addition, thematic synthesis was used to analyse the findings. The study analysed the gap between programming and demands of 4IR technologies and applications. We uncovered that although there is limited literature on programming in primary schools in South Africa (S.A), the few studies that we came across are coming up with many ways of introducing programming to students, plugged and unplugged. These are being administered as game-based, teacher instruction-based, collaboration and /or individual teaching methods. And this is gradually adding to the computational thinking and basic programming skills need by students to be able to tackle the development of AI/AR/VR tools and applications.